Perbedaan Kreativitas Ditinjau dari Pola Asuh Orang Tua pada Anak TK di Desa Kemasan Polokarto Sukoharjo Tahun Ajaran 2015/2016 - Fathimah, Aisyiyah Siti (2016)
The purpose of this research was to determine the difference of creativity in terms of parenting parents on kindergarten children in the village Kemasan, Polokarto, Sukoharjo. This research is a comparative descriptive. Data collection techniques such as questionnaires. The population in this study as many as 124 person, and sample as many as 102 (standard error of 1%). The technique of sampling using proportional random sampling.Analysis of the results using statistical analysis techniques One Way Anova. The results show the value of 153.793 F count> F table at 3.09 and 0.000 sig. probability value <0.05, so that Ho refused and Ha accepted means there is a difference. The highest level of creativity with an average value 50,03 is permissive parenting. The authoritarian parenting has an average value 35,78 and democratic parenting has an average value 43,27.